2014
DOI: 10.1007/s00425-013-2024-8
|View full text |Cite
|
Sign up to set email alerts
|

Plant defense response against Fusarium oxysporum and strategies to develop tolerant genotypes in banana

Abstract: breeding, transgenic and cisgenic approaches have been discussed. This would help us to understand host defenses against Fusarium oxysporum and to formulate strategies to develop tolerant cultivars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 143 publications
1
61
0
4
Order By: Relevance
“…Fusarium oxysporum is a widespread necrotrophic fungus that affects several crops. The fungus infection uses an oxidative burst that serves as a weapon; it triggers nutrient leakage from the host cells allowing the pathogen to survive from dead tissues causing significant crop losses [21]. In the present work, we observed that transgenic plants of tobacco showed different expression levels of OxDC gene, which might be associated to different fungus tolerance levels.…”
Section: 23rt-pcr Oxdc Expression Analysis In T 1 Transgenic Lineagessupporting
confidence: 49%
“…Fusarium oxysporum is a widespread necrotrophic fungus that affects several crops. The fungus infection uses an oxidative burst that serves as a weapon; it triggers nutrient leakage from the host cells allowing the pathogen to survive from dead tissues causing significant crop losses [21]. In the present work, we observed that transgenic plants of tobacco showed different expression levels of OxDC gene, which might be associated to different fungus tolerance levels.…”
Section: 23rt-pcr Oxdc Expression Analysis In T 1 Transgenic Lineagessupporting
confidence: 49%
“…ROS can be involved in HR to produce cell death, in crosslinking with glycoproteins to reinforce the cell wall, or couple with other signaling factors to induce SAR (Torres et al, 2006; Xiao et al, 2013; Swarupa et al, 2014). The first step in ROS production is mediated by NADPH oxidase/RBO (Torres et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…These increases in the control treatments occurred two weeks after the increase in the group of plants treated with 1 and 2% EA. Increases in SA content were between 2 and 5 times higher than the basal values reported in plants at the onset of flowering, and in plants infected with necrotic pathogens such as Fusarium oxysporum (Swarupa et al, 2014). This fact may explain the increase in SA content in the control plants from week five to seven.…”
Section: Cuantificación De áCido Salicílico (As)mentioning
confidence: 72%
“…Estos incrementos en los controles, se presentaron dos semanas posterior al incremento que se presentó en el grupo de plantas tratadas con el EA al 1 y 2%. Los incrementos en el contenido de AS entre 2 a 5 veces los valores basales, son reportados en plantas durante el inicio de la floración, así como en plantas infectadas con patógenos necróticos como Fusarium oxysporum (Swarupa et al, 2014). Pudiendo ser esta la razón de los incrementos del AS en las plantas control en las semanas de la quinta a la séptima.…”
Section: Fully Bilingualunclassified